Altered Global Brain Functional Connectivity in Drug-Naive Patients With Obsessive-Compulsive Disorder - Cui, Guangcheng; Ou, Yangpan; Chen, Yunhui; Lv, Dan; Jia, Cuicui; Zhong, Zhaoxi; Yang, Ru; Wang, Yuhua; Meng, Xin; Cui, Hongsheng; Li, Chengchong; Sun, Zhenghai; et al. (Frontiers in Psychiatry, 2020)
Abnormal functional connectivity (FC) within discrete brain networks is involved in the pathophysiology of obsessive–compulsive disorder (OCD) with inconsistent results. In the present study, we investigated the FC patterns of 40 drug-naive patients with OCD and 38 healthy controls (HCs) through an unbiased voxel-wise global brain FC (GFC) analysis at rest. Compared with HCs, patients with OCD showed decreased GFC within the default mode network (DMN) (i.e., left posterior cingulate cortex /lingual gyrus) and sensorimotor network (i.e., left precentral gyrus/postcentral gyrus) and increased GFC within the executive control network (ECN) (i.e., left dorsal lateral prefrontal cortex and left inferior parietal lobule). Receiver operating characteristic curve analyses further indicated that the altered GFC values within the DMN, ECN, and sensorimotor network may be used as neuroimaging markers to differentiate patients with OCD from HCs. These findings indicated the aberrant FC patterns of the DMN, ECN, and sensorimotor network associated with the pathophysiology of OCD and provided new insights into the changes in brain organization function in OCD.